MỤC LỤC
Viết số phức sau dưới dạng lượng giác $\Large z=\dfrac{(1-i)^{10}}{(\sqrt{3}+1)^{6}}$
Lời giải chi tiết:
Ta có
$\Large \begin{array}{l}
1-i=\sqrt{2}\left(\cos \left(-\frac{\pi}{4}\right)+i \cdot \sin \left(-\frac{\pi}{4}\right)\right) \\
\Rightarrow(1-i)^{10}
\end{array}$
$\Large \begin{array}{l}
=\sqrt{2}^{10} \cdot\left[\cos \left(-10 \cdot \frac{\pi}{4}\right)+i \cdot \sin \left(-10 \cdot \frac{\pi}{4}\right)\right] \\
=2^{5}\left[\cos \left(\cdot \frac{5 \pi}{2}\right)+i \cdot \sin \left(-\frac{5 \pi}{2}\right)\right]
\end{array}$
Lại có
$\Large \begin{array}{l}
\sqrt{3}+i=2\left(\cos \frac{\pi}{6}+i \cdot \sin \frac{\pi}{6}\right) \\
\Rightarrow(\sqrt{3}+i)^{9}=2^{9} \cdot\left(\cos 9 \cdot \frac{\pi}{6}+i \cdot \sin 9 \cdot \frac{\pi}{6}\right)
\end{array}$
$\Large =2^{9} \cdot\left(\cos \frac{3 \pi}{2}+i \cdot \sin \frac{3 \pi}{2}\right)$
Do đó
$\Large \begin{array}{l}
z=\frac{(1-i)^{10}}{(\sqrt{3}+1)^{9}} \\
=\frac{2^{5} \cdot\left[\cos \left(\frac{-5 \pi}{2}\right)+i \cdot \sin \left(\frac{-5 \pi}{2}\right)\right]}{2^{9} \cdot\left(\cos \frac{3 \pi}{2}+i \cdot \sin \frac{3 \pi}{2}\right)} \\
=\frac{1}{2^{4}}(\cos (-4 \pi)+i \cdot \sin (-4 \pi))
\end{array}$
Chọn A
Xem thêm các bài tiếp theo bên dưới